Modeling the magnetic isotherms of (La0.56Ce0.14)Sr0.30MnO3 by a mean-field scaling method and estimation of magnetic entropy change - Yahyaoui, S.
We report a study on the magnetic properties of the (La0.56Ce0.14)Sra(0).30MnO3 perovskite, by a mean-field method. By scaling of the experimental magnetization data, the mean-field exchange parameter lambda and the B-s function of the equation of state B-s [(H + H-exch)/T] are directly determined, as well as the order of the phase transition. The spin quantum number of the manganite has been also determined. The mean-field scaling has been used to estimate magnetic entropy change (-Delta S-M) within the thermodynamics of the model and without using the usual numerical integration of a Maxwell relation. The maxima of the positive absolute value of (-Delta S-M) upon variation of the applied magnetic field at 1 and 5 T are about 1.68 and 5.04 J kg(-1) K-1, respectively Satisfactory agreement between the mean-field model and experimental behavior has been found. (C) 2015 Elsevier B.V. All rights reserved.